Stakeholders’ perspectives on integrating the management of depression into routine HIV care in Uganda: qualitative findings from a feasibility study - Rutakumwa, Rwamahe; Ssebunnya, Joshua; Mugisha, James; Mpango, Richard Steven; Tusiime, Christine; Kyohangirwe, Leticia; Taasi, Geoffrey; Sentongo, Hafsa; Kaleebu, Pontiano; Patel, Vikram; Kinyanda, Eugene (International journal of mental health systems, 2021)
HIV/AIDS continues to be a major global public health problem with Eastern and Southern Africa being the regions most affected. With increased access to effective antiretroviral therapy, HIV has become a chronic and manageable disease, bringing to the fore issues of quality of life including mental wellbeing. Despite this, the majority of HIV care providers in sub-Saharan Africa, including Uganda’s Ministry of Health, do not routinely provide mental health care including depression management. The purpose of this paper is to explore stakeholders’ perspectives on the feasibility and acceptability of integrating depression management into routine adult HIV care. The paper addresses a specific objective of the formative phase of the HIV + D study aimed at developing and evaluating a model for integrating depression management into routine HIV care in Uganda. Methods: This was a qualitative study. Data were collected through in-depth interviews with 11 patients at enrollment and follow-up in the pilot phase, and exit interviews with 11 adherent patients (those who completed their psychotherapy sessions) and six non-adherent patients (those missing at least two sessions) at the end of the pilot phase. Key informant interviews were held with four clinicians, five supervisors and one mental health specialist, as were three focus group discussions with lay health workers. These were purposively sampled at four public health facilities in Mpigi District. Data were analysed thematically. Results: Patients highlighted the benefits of treating depression in the context of HIV care, including improved adherence to antiretroviral therapy, overcoming sleeplessness and suicidal ideation, and regaining a sense of selfefficacy. Although clinicians and other stakeholders reported benefits of treating depression, they cited challenges in managing depression with HIV care, which were organisational (increased workload) and patient related (extended waiting time and perceptions of preferential treatment). Stakeholders generally shared perspectives on how best to integrate, including recommendations for organisational level interventions–training, harmonisation in scheduling appointments and structural changes–and patient level interventions to enhance knowledge about depression. Conclusions: Integrating depression management into routine HIV care in Uganda is acceptable among key stakeholders, but the technical and operational feasibility of integration would require changes both at the organisational and patient levels.
Keywords: Depression; HIV; ART; Mental health; Uganda